CNP Promotes Antiarrhythmic Effects via Phosphodiesterase 2. Issue 4 (30th January 2023) - Cachorro, Eleder; Günscht, Mario; Schubert, Mario; Sadek, Mirna S.; Siegert, Johanna; Dutt, Fabian; Bauermeister, Carla; Quickert, Susann; Berning, Henrik; Nowakowski, Felix; Lämmle, Simon; Firneburg, Rebecca; et al.
Abstract : Background: Ventricular arrhythmia and sudden cardiac death are the most common lethal complications after myocardial infarction. Antiarrhythmic pharmacotherapy remains a clinical challenge and novel concepts are highly desired. Here, we focus on the cardioprotective CNP (C-type natriuretic peptide) as a novel antiarrhythmic principle. We hypothesize that antiarrhythmic effects of CNP are mediated by PDE2 (phosphodiesterase 2), which has the unique property to be stimulated by cGMP to primarily hydrolyze cAMP. Thus, CNP might promote beneficial effects of PDE2-mediated negative crosstalk between cAMP and cGMP signaling pathways. Methods: To determine antiarrhythmic effects of cGMP-mediated PDE2 stimulation by CNP, we analyzed arrhythmic events and intracellular trigger mechanisms in mice in vivo, at organ level and in isolated cardiomyocytes as well as in human-induced pluripotent stem cell-derived cardiomyocytes. Results: In ex vivo perfused mouse hearts, CNP abrogated arrhythmia after ischemia/reperfusion injury. Upon high-dose catecholamine injections in mice, PDE2 inhibition prevented the antiarrhythmic effect of CNP. In mouse ventricular cardiomyocytes, CNP blunted the catecholamine-mediated increase in arrhythmogenic events as well as in ICaL, INaL, and Ca 2+ spark frequency. Mechanistically, this was driven by reduced cellular cAMP levels and decreased phosphorylation of Ca 2+ handling proteins. Key experiments were confirmed in human iPSC-derived cardiomyocytes. Accordingly, the protective CNP effects were reversed by either specific pharmacological PDE2 inhibition or cardiomyocyte-specific PDE2 deletion. Conclusions: CNP shows strong PDE2-dependent antiarrhythmic effects. Consequently, the CNP-PDE2 axis represents a novel and attractive target for future antiarrhythmic strategies.